1986
DOI: 10.1182/blood.v67.1.31.bloodjournal67131
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic (recombinant) human granulocyte-macrophage colony- stimulating factor: effect on normal bone marrow and leukemia cell lines

Abstract: To examine the biologic properties of the molecule encoded by the human gene for granulocyte-macrophage colony-stimulating factor (GM-CSF), we expressed the cloned complementary DNA (cDNA) in transfected monkey COS cells and purified the resultant protein. Purified biosynthetic human GM-CSF was added to cultures of normal hematopoietic progenitor cells in semisolid media, and the resulting colonies were characterized cytochemically. Non-adherent light-density bone marrow cells from healthy adult volunteers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
9
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
3
9
0
Order By: Relevance
“…We have shown that rhGM-CSF alone did not induce human burst formation and could not augment the effect of rhEpo on human BFU-e growth. In this regard, earlier reports on murine [25] and human [24, cultures are controversial in that only some investigators are in agreement with our results [25,26]. On the other hand, other investigators have reported that GM-CSF stimulates BFU-e in the presence of Epo, or has BPA [24,[27][28][29][30][31].…”
Section: Discussonsupporting
confidence: 90%
“…We have shown that rhGM-CSF alone did not induce human burst formation and could not augment the effect of rhEpo on human BFU-e growth. In this regard, earlier reports on murine [25] and human [24, cultures are controversial in that only some investigators are in agreement with our results [25,26]. On the other hand, other investigators have reported that GM-CSF stimulates BFU-e in the presence of Epo, or has BPA [24,[27][28][29][30][31].…”
Section: Discussonsupporting
confidence: 90%
“…Although HL60 (Ruscetti et al, 1981) and KGI cells (Lusis & Koeffler, 1980) initially proliferated in response to CSF, they lost this property with serial culture (Taetle et al, 1983a;Ruscetti et al, 1981). Recent studies confirm that these cell lines proliferate in response to purified, recombinant (GM)-CSF (Tomonaga et al, 1986). Our HL60 cells never showed CSF responses in liquid or colony culture.…”
Section: Discussionsupporting
confidence: 66%
“…The HL-60 cell line, established from the blood leukocytes of a patient with acute progranulocytic leukemia, has been widely used to study factors influencing the growth and maturation of myeloid cells (Gallagher et al, 1979;KoeMer and Golde, 1980;Olsson and Olofsson, 1981;Taketazu et al, 1984). Despite these efforts, questions remain concerning the relative contributions of the various granulocytelmacrophage colony-stimulating factors (M-, GM-, G-CSFs) (Ruscetti et al, 1981;Metcalf, 1983;Tomonaga et al, 1986) and autocrine mediators other than CSFs Perkins et al, 1984;Heil and Chiao, 1985) to HL-60 growth, and their interactions, if any, with chemical inducers of maturation (Elias et al, 1980). This is particularly true of highly passaged populations, which, in contrast to their earlier counterparts, are highly proliferative, induction resistant, and capable of growing autonomously even at very low cell densities (Gallagher et al, 1979;Brennan et al, 1981).…”
mentioning
confidence: 99%